2019
DOI: 10.1001/jamanetworkopen.2019.14325
|View full text |Cite
|
Sign up to set email alerts
|

Geographical Variation in Outcomes of Primary Hip and Knee Replacement

Abstract: Key PointsQuestionAre hospital organizational factors, surgical factors, and patient factors associated with patient outcomes and National Health Service costs for total hip and knee replacement?FindingsThis cohort study of more than 383 000 patients in 207 health areas in England identified significant health area–level variation in patient outcomes for total hip and knee replacement surgery. Geographical variation was associated with better outcomes for surgical procedures in private and high-volume hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 25 publications
0
15
0
1
Order By: Relevance
“…Variables such as year of surgery, the surgeon, and the hospital could potentially confound the relationship between THA dislocation and HCRU/cost given published evidence regarding variation in care and within-region/hospital constancy for THA. [13][14][15] Data on baseline provider characteristics indicated that, prior to matching, a greater proportion of patients with THA dislocation were identified from hospitals with lower hospital and surgeon volume.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Variables such as year of surgery, the surgeon, and the hospital could potentially confound the relationship between THA dislocation and HCRU/cost given published evidence regarding variation in care and within-region/hospital constancy for THA. [13][14][15] Data on baseline provider characteristics indicated that, prior to matching, a greater proportion of patients with THA dislocation were identified from hospitals with lower hospital and surgeon volume.…”
Section: Discussionmentioning
confidence: 99%
“…Patients were matched directly on the year of THA, surgeon, and the hospital for THA as it has been shown that these characteristics are important determinants of HCRU given evidence regarding variation in care and within-region/hospital constancy for THA. [13][14][15] Propensity score matching was then used to match for all other covariates using nearest neighbor technique with calipers of width equal to 0.2 of the pooled standard deviation of the logit of the propensity score. Standardized differences were evaluated to assess and ensure the balance…”
Section: Study Analysesmentioning
confidence: 99%
“…While there is the burgeoning literature which applies geospatial analysis or assesses geographic patterns for health outcomes of interest, in general, geospatial analysis is still underutilized for clinical research. 44,[51][52][53][54] Geospatial analysis findings (MHCs as a geographic risk factor for AEs) may not be captured via conventional quantitative analysis, which typically relies on a priori list of variables.…”
Section: Discussionmentioning
confidence: 99%
“…[25][26][27][28] Currently, these procedures are performed in a variety of hospital settings, with variation in the utilization of services, and reimbursement rate deviations across commercial payers and geographical regions. [29][30][31] This research explores the relationship between elective hip and knee procedure quality outcomes-measured by frequency of clinical complications, readmissions, and prolonged length of stay-and the median hospital-level commercial payments for the hospitalization. Specifically, we seek to determine if higher-paid hospitals have higher quality outcomes compared to those receiving lower payments, after accounting for clinical and market-level factors.…”
Section: Introductionmentioning
confidence: 99%